Meat makes people powerful : a global history of the modern era - Warren, Wilson J., 1960- (University of Iowa Press, 2018)
From large-scale cattle farming to water pollution, meat - more than any other food - has had an enormous impact on our environment. Historically, Americans have been among the most avid meat-eaters in the world, but long before that meat was not even considered a key ingredient in most civilizations' diets. The author, a labor historian who has studied the meat industry for more than a decade, provides this global history of meat to help us understand how it entered the daily diet, and at what costs and benefits to society. Spanning from the nineteenth century to current and future trends, the author walks us through the economic theory of food, the discovery of protein, the Japanese eugenics debate around meat, and the environmental impact of livestock, among other topics. This text provides readers with the political, economic, social, and cultural factors behind meat consumption over the last two centuries. With a special focus on East Asia, the book reveals how national governments regulated and oversaw meat production, helping transform virtually vegetarian cultures into major meat consumers at record speed. As more and more Americans pay attention to the sources of the meat they consume, this book will help readers not only better understand the industry, but also make more informed personal choices.